Effects of Thought Stopping Therapy on Anxiety in the Elderly Facing the Covid 19 Pandemic in Elderly Home - Niken Yuniar Sari; Budi Antoro; Maria Septijantini Alie (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Thought stopping is a therapy that can help stop disruptive thoughts from changing the thought process. This study aims to determaine the influence of thought stopping therapy on anxiety in the elderly facing the Covid 19 Pandemic in Elderly home . This study used quasi eksperimental design with pre- post test with control group. Responden were 70 people that devided into two group. They were 35 as intervention group that received thought stopping and 35 as control group that received nursing therapy of anxiety. Result showed anxiety in the intervention group decreased from moderate anxiety to mild anxiety and control group decreased still in the moderate anxiety. Thought stopping decreased physiologic, cognitive, behaviour and emotional responses of anxiety significantly (p value <0,05). thought stopping therapy was recommended as therapy to solve the anxiety at home elderly and community.